A Two-Allele Polymorphism in Protein C Inhibitor with Varying Frequencies in Different Ethnic Populations - Radtke, Klaus-P; Greengard, Judith S; Fernández, José A; Villoutreix, Bruno O; Griffin, John H (Thrombosis and Haemostasis, 1996)
cDNAs for protein C inhibitor (PCI), prepared from human liver RNA, contained two forms of PCI, designated PCI*A and PCPB1. While PCI*A is identical to the published PCI sequence, PCPB differs in 4 of 1221 bp and two amino acids, A36V and K86E. Frequencies for the PCI*B allele, determined from genomic DNA, differed among ethnic groups. Frequency distribution and historical migration of modem man suggest that PCI*A arose from the PCI*B allele. Antigen levels in plasma homozygous for PCI*A or PCI*B equalled that of pooled normal plasma. K86E in PCI*B causes a charge alteration in helix D which is likely involved in heparin binding in antithrombin III but not likely involved in glycosaminoglycan binding in PCI. Kinetic studies showed that plasmas homozygous for PCI*A and PCPB are similar in their APC inhibiting properties and in their heparin sensitivity, consistent with the idea that helix D in PCI is not involved in heparin binding